THE EFFECTS OF PANAX GINSENG ROOT EXTRACT ON CARBOHYDRATE AND LIPID DISTURBANCES ASSOCIATED WITH ALLOXAN-INDUCED DIABETIC RATS - M. Naseem; El-Hassane Nazih; K. Ouguerram; I. Rabbani; H. Zaneb; H. U. Rehman; I. Masood; J. M. Huvelin; M. S. Yousaf; S. K. Tahir (Journal of Animal and Plant Sciences, 2016)
Diabetes is a major public health issue. Panax ginseng is an anciently used herbal drug for diabetic treatment. Anti-diabetic effects of P. ginseng are attributed to ginsenosides. The objective of current study is to determine the anti-diabetic effects of Panax ginseng root extract at gene level.  Rats were fed on high-fatty diet for two weeks and divided into three groups (8rats/group): Non-diabetic control group (NDG), Diabetic-group (DG), Diabetic+300mg/kg Panax ginseng root extract group (DM+PGE). On 14th day, the rats were kept in overnight-fasting and administered single intra-peritoneal injection of alloxan-monohydrate dissolved in 0.5ml of saline solution at the dose of 120-130mg/Kg body weight (BW). BW and blood glucose were measured on 1st and 14th week. After 14 weeks, fasting/basal blood samples were collected for the biochemical analysis. Liver, skeletal muscle and adipose tissue were also collected for mRNA genes expression of Glucose transporter-4 (GLUT-4), Insulin receptor substrate-1(IRS-1), Insulin receptor (IR), Sterol regulatory element binding protein-1c (SREBP-1c), Fatty acid sythase (FAS), Peroxisome proliferator-activated receptor-α (PPAR-α), Peroxisome proliferator-activated receptor-γ (PPAR-γ) and tumor necrosis factor-α (TNF-α). We found a significant reduction in the BW of DM+PGE group at 14th week. Glycemia was significantly higher in DG and significant reduction was recorded in DM+PGE group. While serum glucose, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and creatinine levels decreased significantly in treated groups. We observed significant increase for catalase (CAT) and decrease for malondialdehyde (MDA) in DM+PGE group in comparison to DG. PGE showed significant increase for HDL-C and decrease for TG. PGE significantly down-regulate hepatic TNF-α. For skeletal muscle, we recorded significant up-regulation for GLUT-4 and PPAR-α while for adipose tissue, we measured up-regulation for IRS-1 and PPAR-γ and significant down-regulation was recorded for TNF-α. In conclusion, PGE has strong anti-diabetic effects mediated by a modulating effect on involved key genes.
Keywords: Carbohydrate and lipid metabolism; Diabetes mellitus; Panax ginseng root extract; Rats